2019
DOI: 10.1111/anu.12915
|View full text |Cite
|
Sign up to set email alerts
|

Spent brewer's yeast as a replacement for fishmeal in diets for giant freshwater prawn (Macrobrachium rosenbergii), reared in either clear water or a biofloc environment

Abstract: A 90‐day feeding experiment was conducted in order to test spent brewer's yeast as a replacement for fishmeal in diets for giant freshwater prawn (Macrobrachium rosenbergii) reared in either a recirculating aquaculture system (RAS) or a biofloc system. Triplicate groups, each of 20 prawn (6.7 ± 0.03 g), were randomly assigned to 24 identical tanks. Twelve tanks were connected to the RAS, and the other 12 tanks were connected to the biofloc system which were initially supplemented with Bacillus subtilis, molass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Despite the high level of protein in the diets, lipids were reported to contribute to the highest growth performance of juvenile Fenneropenaeus indicus (Sarlin & Philip, 2016). Besides, high dietary protein led to maximum growth of juvenile pearl oyster Pinctada fucata martensii (Yang et al, 2017) and giant freshwater prawn Macrobrachium rosenbergii (Nguyen et al, 2019), which was in agreement with the present study. González-Félix et al (2002) evaluated different neutral lipids, which resulted in different effects on growth performance, survival rate, and the lipid's potential interaction and nutrition of shrimp muscle tissue of juvenile L. vannamei.…”
Section: Journal Of Sustainabilitysupporting
confidence: 91%
“…Despite the high level of protein in the diets, lipids were reported to contribute to the highest growth performance of juvenile Fenneropenaeus indicus (Sarlin & Philip, 2016). Besides, high dietary protein led to maximum growth of juvenile pearl oyster Pinctada fucata martensii (Yang et al, 2017) and giant freshwater prawn Macrobrachium rosenbergii (Nguyen et al, 2019), which was in agreement with the present study. González-Félix et al (2002) evaluated different neutral lipids, which resulted in different effects on growth performance, survival rate, and the lipid's potential interaction and nutrition of shrimp muscle tissue of juvenile L. vannamei.…”
Section: Journal Of Sustainabilitysupporting
confidence: 91%
“…Crustaceans generally have a higher FCR compared with fish due to their slower feeding rates and tendency of masticating food items (Romano & Zeng, 2017). When culturing M. rosenbergii in a tank-based biofloc system, a FCR of 2.25 was reported by Ballester et al (2017), while higher FCR values of 4.49 were found by Nguyen et al (2019). A reduction to feeding rates may actually decrease FCR and improve cost-effectiveness when using BFT, but this requires more investigations.…”
Section: Growth Performance and Feed Conversion Ratiomentioning
confidence: 99%
“…In a study with black tiger shrimp (Penaeus monodon), they found an improved survival and immune response of shrimp fed 100 g/kg of Candida aquaetextoris [170]. In a study with giant freshwater prawn (Macrobrachium rosenbergii), they found similar growth, FCR and protein retention in shrimp fed up to 155 g/kg in both clear and biofloc systems, although growth and feed efficiency were reduced when fed 300 g/kg only in the clear water system [171].…”
Section: Shrimpmentioning
confidence: 99%